Dyslipidemia-associated atherogenic oxidized lipids induce platelet hyperactivity through phospholipase Cγ2-dependent reactive oxygen species generation. (19th May 2019) - Berger, Martin; Wraith, Katie; Woodward, Casey; Aburima, Ahmed; Raslan, Zaher; Hindle, Matthew S.; Moellmann, Julia; Febbraio, Maria; Naseem, Khalid M.
Abstract: Oxidized low-density lipoprotein (oxLDL) and associated oxidized phosphocholine-headgroup phospholipids (oxPCs) activate blood platelets through ligation of the scavenger receptor CD36. Previously, we found that oxLDL stimulated phosphorylation of phospholipase Cγ2 (PLCγ2). However, the functional relevance of PLCγ2 phosphorylation in oxLDL-mediated platelet hyperactivity remained elusive. Here, we set out to explore the functional importance of PLCγ2 in oxLDL-mediated platelet activation using human and genetically modified murine platelets. The CD36-specific oxidized phospholipid (oxPCCD36 ) triggered the generation of reactive oxygen species (ROS) in platelets under static and arterial flow conditions. The ROS generation in response to oxPCCD36 was sustained for up to 3 h but ablated in CD36- and PLCγ2-deficient platelets. The functional importance of ROS generation in response to atherogenic lipid stress was examined through measurement of P-selectin expression. OxPCCD36 induced P-selectin expression, but required up to 60 min incubation, consistent with the timeline for ROS generation. P-selectin expression was not observed in CD36- and PLCγ2-deficient mice. The ability of oxPCCD36 and oxLDL to stimulate P-selectin expression was prevented by incubation of platelets with the ROS scavenger N-acetyl-cysteine (NAC) and the NOX-2 inhibitor gp91ds-tat, but not with the NOX-1 inhibitor ML171. In summary, we provide evidence that prolonged exposure to oxLDL-associated oxidized phospholipids induces platelet activation via NOX-2-mediated ROS production in a CD36- and PLCγ2-dependent manner.